Making Of Notary Deeds in An Emergency Period in Indonesia - Afif Khalid (LAFADZ JAYA Publisher, 2023)
A notarial deed is authentic, so its manufacture must meet formal requirements such as Article 16 paragraph (1) letter m UUJN. This study aimed to determine whether the provisions of Article 16 paragraph (1) letter m of the UUJN can be fulfilled during an emergency such as the Covid-19 pandemic and whether the making of a notary deed can be done electronically. To discuss these problems, normative legal research is used, namely research on secondary data in the form of primary, secondary, and tertiary legal materials. The legal materials were collected through a literature study, then processed and analyzed descriptively and qualitatively. The study results show that the provisions of Article 16 paragraph (1) letter m UUJN must be fulfilled even in emergency conditions such as the Covid-19 pandemic because it involves the authenticity of the notary deed. Then, a notarial deed cannot be done electronically because the normative juridical UUJN does not regulate this problem.